2017
DOI: 10.3390/molecules22091429
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Metal Binding in the Amyotrophic Lateral Sclerosis-Related Aggregation of Copper-Zinc Superoxide Dismutase

Abstract: Protein misfolding and conformational changes are common hallmarks in many neurodegenerative diseases involving formation and deposition of toxic protein aggregates. Although many players are involved in the in vivo protein aggregation, physiological factors such as labile metal ions within the cellular environment are likely to play a key role. In this review, we elucidate the role of metal binding in the aggregation process of copper-zinc superoxide dismutase (SOD1) associated to amyotrophic lateral sclerosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(27 citation statements)
references
References 103 publications
0
26
0
Order By: Relevance
“…The electrostatic loop is composed of positively charged amino-acids that guide superoxide radicals into the SOD1 active site where the copper ion is located [ 41 ]. The metal-binding loop coordinates the binding of Zinc and Copper ions [ 42 , 43 ], which is structurally important for SOD1 [ 44 ]. These loops together shape the active site pocket [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…The electrostatic loop is composed of positively charged amino-acids that guide superoxide radicals into the SOD1 active site where the copper ion is located [ 41 ]. The metal-binding loop coordinates the binding of Zinc and Copper ions [ 42 , 43 ], which is structurally important for SOD1 [ 44 ]. These loops together shape the active site pocket [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…The increased ROS production, among which the superoxide anion, and the interaction with cell signaling pathways are possibly responsible of DNA damage and apoptosis of motor neurons. Thus, it is suggested that mutations do not cause ALS via loss of function, rather than through the alternate toxic gain of function (Hilton et al, 2015;Sirangelo and Iannuzzi, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Over 25 genes have been identified either as the genetic cause of the disease in the familial cases, or as genetic variants influencing predisposition in sALS, the most common form of the disease [34,35]. Proteins encoded by some of these genes require manganese, copper, and zinc as cofactors for their enzymatic activity, or are interrelated to other elemental pathways [36]. Previous studies have largely relied on elemental biomarkers or surrogate estimates of exposure at a few time points after diagnosis [34].…”
Section: Plos Computational Biologymentioning
confidence: 99%